RNA viruses - Cann, Alan J. (Oxford University Press, 2000)
This book provides a broad treatment of the principles and practice of RNA virus research to insure the widest possible audience. It is perfect for laboratories involved in virus culture, including both academic and industrial research groups and public health laboratories